3D Brain image segmentation using 3D tiled convolution neural networks - Haque, Md Mahibul; Ria, Jobeda Khanam; Mannan, Fahad Al; Majumder, Sadman; Uddin, Md Reaz (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.